Congenital Rubella Syndrome in 3 schools for deaf and/or blind children in Lima, Cusco and Arequipa, Peru, 1998-2000 - Blitchtein Winicki, Dora (2002)
OBJECTIVE: To determine the presence of congenital rubella syndrome (CRS) in three Peruvian cities. DESIGN: Transversal, descriptive study. MATERIAL AND METHODS: Children under twelve years old with major definition criteriae of congenital rubella syndrome receiving special education in Lima (three), Cusco (two) and Arequipa (one) schools, from 1998 to 2000, were included. RESULTS: From 364 children 105 were included, 61% of cases suspicious, 21% probable and 1,9% confirmed; 64,7% had central nervous system manifestations, 31% ocular manifestations, 18% at least two clinical manifestations. CONCLUSIONS: Probable and confirmed cases of CRS represented 6,6% of all children receiving special education, evidencing that CRS represents a health problem in our country and the need to initiate anti-rubella vaccination in Peru.